Formulasi Sediaan Lipstik Ekstrak Bunga Rosella (Hibiscus sabdariffa) sebagai Pewarna dan Minyak Zaitun (Olive oil) sebagai Emolien - Asfy Nurany; Andi Sri Suriati Amal; Solikah Ana Estikomah (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2018)
Islam is a beautiful religion and loves beauty. The using of a lipstick is to form a lip in an attractive appearance and to protect the lips from dryness with no side effects. The use of rosella as a dye and olive oil as an emollient in the formulation of the preparations due to the red pigments of anthocyanin in rosella (Hisbiscus sabdariffa l.) and olive oil can be used as an emollient to keep the moisture of the lips. The purpose of this study was to make a lipstick with a good stability. The simplisia of rosella flowers was macerated in ethanol 96%. The components of the lipstick used are cera alba petroleum jelly, aba, Cetyl alcohol, lanolin, titanium dioxide, nipagin, oleum rosae, olive oil and extracts of flowers rosella with concentrations of 0%, 2%, 4%, 6%, 8%, 10%. The lipstick mixture was then tested including: homogeneity, stability, grease, melting point and pH tests. Test a fondness and irritation test performed on the 25 panelists. The results showed that the concentrations of rosella extract 0% did not cause any color or white, the concentration of 2%-4% color posed red fade, the concentration of 6% was red, the concentration of 8%-10% was dark red. Concentration of the extract of 0%-4% did not experience the color change (stable) in a storage room temperature for 30 days. As for the material of 6%-10% color lipstick changes slowly, due to the occurrence of oxidation on lipstick. The result of fondness and irritation tests are that in the preparation of 1, 2, 3, 4, 5 and 6 does not cause irritation, itching and skin redness on the skin.